Current Concepts in the Etiology and Treatment of Keloids - Naylor, Michelle C.; Brissett, Anthony E. (Facial Plastic Surgery, 2012)
Keloids are benign, fibroproliferative growths that occur as a result of dermal injury in ~15% of the population. They are characterized by their extension beyond the confines of the original injury and often present with pain and pruritus. Additionally, these growths may result in cosmetic deformities and contribute to significant emotional distress. It is thought that keloids form as a result of aberrancies in the normal wound-healing process, which is complex and involves an elegant interplay between multiple cell types, cytokines, and proteins. The exact etiology is unknown, but significant research efforts have been made. These efforts have revealed that various cell types in keloids are either hyperresponsive and/or overproductive of various growth factors. Additionally, keloid cell types respond differently to mechanical strain than skin cells in patients who do not form keloids. This lack of understanding of keloid pathophysiology has left the care provider with a lack of a single definitive treatment strategy. Instead, a multitude of therapies exist ranging from surgery to injectables to lasers and any combination thereof. This purpose of this article is to highlight our current knowledge and emerging scientific understanding of keloid pathology and the current management strategies.
Keywords: keloid; hypertrophic scars; treatment; scar